Identifikasi Dan Analisis Senyawa Metabolit Sekunder Ekstrak Daun Sicerek (Clausena excavata) - Maidawati, Maidawati (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2022)
Clausenaexcavata is a plant that is widespread in tropical regions including Indonesia. This study aims to identify the compounds of secondary metabolites found in clausenaexcavata leaf extract as a reference for Indonesian medicinal plant halls and possible applications in the field of engineering like corrosion inhibitors. FTIR analysis has been used to determine the functional groups contained in the methanol extract of Sicerek (Clausena excavata) leaves. The results of identification and analysis of FTIR spectrum showed that the methanol extract of Clausenaexcavata contained O-H, N-H, C-N, C-H, C-O functional groups leaves contained phenolic compounds, flavonoids, coumarin, alkaloids, saponins and terpenoids.